ICEAP Proceeding Book Vol 1 2018
DOI: 10.26499/iceap.v1i1.81
|View full text |Cite
|
Sign up to set email alerts
|

Padlet: A Technology Tool for the 21st Century Students Skills Assessment

Abstract: Emergence of Internet connected devices and globalization in education has paved way for the new discoveries in the 21st Century Learning. In current classrooms, the students use various instructional technologies to synthesis new knowledge, collaborate with peers, critically solve problems, and make valid decisions to shine in the current, complex and globalized community. Due to the advancement in the technology, it is not an easy task to meet sustainability in education as identifying and deploying the prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 6 publications
0
9
0
1
Order By: Relevance
“…In addition to providing flexibility in time and space in online collaboration in this study, it was remarked that shareability of distinctive stimulants, such as video, image and audio increased writing achievement. A variety of research in the literature confirmed that online collaborative activities proved advantageous for writing achievement (Awaluddin, Karim & Saad, 2017;Alshalan, 2016;Bikowski & Vithanage, 2016;Garnham, Betts & Hole, 2018;Ramachandiran, & Mahmud, 2018) Regarding group interaction, although both groups were comprised of close friends, writing processes and group interactions differed in nature. 2 nd group members experienced a fruitful writing process and group interaction; however, facing a disagreement during F2F collaboration, the 1 st group had a problematic collaboration.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to providing flexibility in time and space in online collaboration in this study, it was remarked that shareability of distinctive stimulants, such as video, image and audio increased writing achievement. A variety of research in the literature confirmed that online collaborative activities proved advantageous for writing achievement (Awaluddin, Karim & Saad, 2017;Alshalan, 2016;Bikowski & Vithanage, 2016;Garnham, Betts & Hole, 2018;Ramachandiran, & Mahmud, 2018) Regarding group interaction, although both groups were comprised of close friends, writing processes and group interactions differed in nature. 2 nd group members experienced a fruitful writing process and group interaction; however, facing a disagreement during F2F collaboration, the 1 st group had a problematic collaboration.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Concerning creativity, participants remarked that they could be more creative on online texts. The literature often addresses collaborative writing on Padlet as improving creativity (DeWitt, Alias & Siraj, 2015, Ramachandiran, & Mahmud, 2018Garnham, Betts & Hole, 2018). Drawing on the data of this study, the relationship between writing on Padlet and creativity can be explained on two points.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Blogs in the scope and features of smaller facilities are known as microblogging, and it is one of the recent technology in the Web 2.0 era [8]. Research conducted by Ebner et al exposes that microblogging media can be regarded as a recent form of communication that can informally support learning outside the classroom [8], enhance critical thinking skills, [9], as well as assessment skills [10].…”
Section: Introductionmentioning
confidence: 99%
“…Padlet is an application that allows users to collaborate with text, photos, videos, or other content. Padlet functions like an online sheet of paper or bulletin board where users can individually and collaboratively place content on a Web page [10], [17]. Concisely, Padlet helps the lecturer to give the task for the students, give comments, and also the whole class can see the result of each college students' work [18] and as well as opportunities for peer learning and selfassessment since students have immediate access to a broad spectrum of responses from classmates rather than a few responses from the vocal ones [19].…”
Section: Introductionmentioning
confidence: 99%
“…Related to the use of online media in learning, currently, microblogging media, which is smaller than a blog, is the latest technology in the web 2.0 era (Ebner, Lienhardt, Rohs, & Meyer, 2010). Research by Ebner et.all indicates, that media microblogging can be seen as a new form of communication that informally to support learning outside the classroom (Ebner et al, 2010) to train critical thinking skills, (Rathakrishnan, Ahmad, & Choi, 2018), as well as skills assessment (Ramachandiran & Mahmud, 2018).…”
Section: Introductionmentioning
confidence: 99%